Pola Asuh Orang Tua di Era Digital - Ananda Rachmaniar (Journal of Education and Counseling (JECO), 2021)
Parenting patterns in the digital era have an important role for children's development. Parents must be careful and precise in determining the pattern of parenting that will be given to their children. Differences in age and gender are a concern in the process of determining the parenting pattern that will be applied to children. Determining parenting patterns must be in accordance with the times and parents must have more control over the use of digital media than their children. The method used in this article is a literature study. This article is expected to provide new insight and understanding about parenting in the digital era and how to choose the right parenting style to be applied in accordance with technological developments that occur.